STAT3-mediated regulation of oxidative-stress responsive genes - Grillo, Michela (2020)
Signal transducer and activator of transcription 3 (STAT3) is a component of the JAK/STAT pathway and a key transcription factor involved in several physiological and pathological processes. The JAK/STAT3 signalling pathway has been extensively studied, and the molecular mechanism leading to its activation by cytokines and the expression of canonical STAT3 target genes are well known. Previous studies from this lab showed that, beyond the canonical pathway, STAT3 is a redox-sensitive transcription factor that can modulate gene expression of non-canonical target genes, such as Kcnb1, in response to cell exposure to Reactive Oxygen Species (ROS) (Palmer 2015). ROS are bona fide intracellular messengers that influence cell metabolism and are known to be released in tissues exposed to ischaemia/reperfusion (I/R); furthermore, STAT3 has an established role in the maintenance of cardiac-cell homeostasis as well as a cardio-protective role in response to ischaemia/reperfusion. Using murine embryonic fibroblast expressing either a WT-STAT3 (STAT3 -/- WT MEFs) or a STAT3 redox insensitive mutant (STAT3 -/- C3S), I have investigated whether the STAT3-mediated expression of Kcnb1, as a representative STAT3-dependent oxidative stress-responsive gene, was also activated in response to ROS released during hypoxia/reoxygenation (H/R). My findings showed that Kcnb1 expression is activated during hypoxia/reoxygenation, is dependent on an oxidative competent form of STAT3, but is not driven by ROS; in fact, Kcnb1 expression is the result of a delayed hypoxic effect. Kcnb1 expression triggered by cell exposure to ROS, as well as by hypoxia, is the result of an unknown molecular mechanism involving cooperation between oxidative-stress competent STAT3 and the hypoxia-inducible factor 1a (HIF-1a). STAT3 ChIP-seq results suggests that unphosphorylated STAT3 (USTAT3) binds chromatin sites mainly localised within intergenic regions, and cell exposure to LIF, with consequent STAT3 activation, disrupt USTAT3 interactions with DNA. Furthermore, STAT3 ChIP and ChIP-seq analysis showed that STAT3 regulation of Kcnb1 is not mediated by STAT3 directly binding to the Kcbn1 promoter, and more generally, ROS do not induce oxidised STAT3 binding to DNA. This indicates that STAT3 is involved in the regulation of oxidative-stress responsive genes through its role as a transducer of signal rather than a transcriptional regulator.